2023
DOI: 10.1037/pro0000519
|View full text |Cite
|
Sign up to set email alerts
|

Examining psychologist prescriptive authority as a cost-effective strategy for reducing suicide rates.

Abstract: Six states (New Mexico, Louisiana, Illinois, Iowa, Idaho, and Colorado) grant prescriptive authority to qualified psychologists, and research has shown that these policies are associated with a reduction in suicides. In this study, we assess the cost-effectiveness of these policies in reducing suicide rates. This study used a Markov model with a time horizon of 20 years to estimate the incremental net monetary benefit (INMB) of the policy from the societal perspective with a simulated cohort of 100,000 people.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Based on our findings, state-level governing bodies should reexamine the policies outlining the scope of practice for psychologists and consider the addition of prescribing authority in a manner similar to New Mexico and Louisiana. Our results suggest that codifying prescribing authority for psychologists would be a step toward achieving the “Triple Aim” of health care (Berwick et al, 2008), especially given that recent studies found that the passage of RxP policies produced cost-effective reductions in mental health-related mortality (Choudhury & Plemmons, 2023; Hughes, McGrath, & Thomas, 2023; Hughes, Phillips, et al, 2023). Such a policy would promote an improvement in the health of the population via more widely available mental health care without necessarily increasing the cost per capita.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on our findings, state-level governing bodies should reexamine the policies outlining the scope of practice for psychologists and consider the addition of prescribing authority in a manner similar to New Mexico and Louisiana. Our results suggest that codifying prescribing authority for psychologists would be a step toward achieving the “Triple Aim” of health care (Berwick et al, 2008), especially given that recent studies found that the passage of RxP policies produced cost-effective reductions in mental health-related mortality (Choudhury & Plemmons, 2023; Hughes, McGrath, & Thomas, 2023; Hughes, Phillips, et al, 2023). Such a policy would promote an improvement in the health of the population via more widely available mental health care without necessarily increasing the cost per capita.…”
Section: Discussionmentioning
confidence: 85%
“…One of the driving factors of this continued debate, as highlighted by McGrath (2020), is that there has been minimal research to date on the patient or workforce outcomes associated with these policies. To date, two studies have demonstrated a decrease in mental health-related mortality following the implementation of these policies (Choudhury & Plemmons, 2023; Hughes, McGrath, & Thomas, 2023) and a third found that this is a cost-effective policy strategy for reducing suicide rates (Hughes, Phillips, et al, 2023); however, the mechanisms underlying those decreases remain unexplored. This study serves as an early step toward empirically estimating the impact of this policy by simulating the changes in the prescriber shortages at the state and national level under policies similar to those enacted in Louisiana and New Mexico.…”
mentioning
confidence: 99%
“…Furthermore, our modeling results provide a first step toward clarifying the role of prescribing psychologists in the mental health workforce in terms of how their patient case mix and initial prescribing choices compare to those of psychiatrists and primary care physicians. Given the relatively limited literature that exists on prescribing psychologists (Choudhury & Plemmons, 2023;Hughes, Phillips, et al, 2023;Linda & McGrath, 2017;Peck et al, 2021), these findings suggest a myriad of future directions and potential policy implications.…”
Section: Discussionmentioning
confidence: 94%
“…Prescribing psychologists are a small but growing workforce, and research to date, although limited, suggests that they positively impact population’s mental health (Choudhury & Plemmons, 2023; Hughes, McGrath, et al, 2023; Hughes, Phillips, et al, 2023). The present study represents the next step in generating a robust body of evidence regarding prescribing psychology by providing the first individual-level description of the patients seen by prescribing psychologists and the medications they receive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation